The role of job crafting in linking empowering leadership and job performance - Sergio L. Peral; Jesse Davidovitz (SA Journal of Industrial Psychology)
Orientation: Job crafting involves employees proactively shaping their job demands and resources, such as physical or relational job boundaries, leading to positive outcomes such as increased meaningfulness and job performance. Leadership is a key catalyst for job crafting within organisations. This study explores how empowering leadership influences job crafting behaviour and, in turn, impacts job performance.